Respuesta :
Answer:
x = - 10, x = - 6
Step-by-step explanation:
x² + 16x + 60 = 0
Consider the factors of the constant term (+ 60) which sum to give the coefficient of the x- ter (+ 16)
The factors are + 10 and + 6 , since
10 × 6 = 60 and 10 + 6 = 16 , then
(x + 10)(x + 6) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 10 = 0 ⇒ x = - 10
x + 6 = 0 ⇒ x = - 6
We have x^2 + 16x + 60 = 0
<=> x^2 + 6x + 10x + 60 = 0
<=> x(x+6) + 10(x+6) = 0
<=> (x+10)(x+6) = 0
<=> x+10=0 or x+6=0
<=> x= -10 or x= -6
Ok done. Thank to me:>
<=> x^2 + 6x + 10x + 60 = 0
<=> x(x+6) + 10(x+6) = 0
<=> (x+10)(x+6) = 0
<=> x+10=0 or x+6=0
<=> x= -10 or x= -6
Ok done. Thank to me:>